A Matlab/Simulink Simulation Small Signal Stability of Single-Machine Infinite Bus Using Optimal Control Based on Load Cluster Patterns - Mado, Ismit; Ruslim; Riyanto, Sugeng (International Journal of Electrical, Energy and Power System Engineering, 2020)
Matlab/Simulink is sophisticated software that has been facilitated by MathWorks Inc. This device is increasingly being used in various fields of research. Likewise, it has great potential in the field of power system simulation. This paper presents a simulation of the optimal performance of the power generation system due to changes in load consumption. Small signal stability due to changes in electrical power usage at the load center is overcome by applying a load cluster pattern. The main objective of this research is to achieve control in a power generation system that is responsive and able to maintain stability in all operating conditions at the load center. Simulation results show the performance of optimal control of the power generation system in each load cluster. Contributions to improve the stability of the power plant system performance by 28.03 percent for frequency (F), 23.03 percent for voltage (V), and 29.5 percent for electric power (P).